Computational Biomechanics of the Wrist Joint - Nazri Bajuri, Mohd.; Abdul Kadir, Mohammed Rafiq; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents an analysis of the stress distribution and contact stresses in severe rheumatoid wrist after total wrist arthroplasty. It assesses and compares the load transfer throughout the joint and contact pressure at the articulations. The data obtained from this study is of importance as this provide greater evidence to the benefits of total wrist arthroplasty in rheumatoid arthritis patients.
Finite element model construction of the healthy wrist.-Biomechanical analysis of the mechanism of the rheumatic wrist -- Biomechanical analysis of the severe rheumatic wrist -- Biomechanical analysis of the wrist arthroplasty in rheumatoid arthritis.
Keywords: Engineering; Orthopedic surgery; Materials; Biomedical engineering; Engineering; Biomedical Engineering; Continuum Mechanics and Mechanics of Materials; Surgical Orthopedics